Strategic Recovery Plan: The Resilience of Wyndham Garden Kuta Beach Bali after Major Impacts of Covid-19 Pandemic - Ratu Agung Bagus Ngurah Putra (International Journal of Glocal Tourism, 2021)
Purpose: This research aims to determine the impacts of the Covid-19 outbreak on the hotel industry in Bali, specifically at Wyndham Garden Kuta Beach Bali. It is to analyze the efforts to overcome with a Strategic Recovery Plan. Research methods: This research is an exploration research with participatory observation used to collect all of the research data. The researcher uses Business Continuity (BC) dan Disaster Recovery (DR) method as reference to understand the map of pandemic effect, determine operational variable and develop Strategic Recovery plan. Findings: The hotel management have formulated six phases of Strategic Recovery Plan consisting of Market Research and Business Strategy, The Top Priorities, Strategic Findings, Set Milestone, Market Segment Projection, and Work Plan. Implication: Those six phases are created to focus business operation on necessary and realistic action that can be implemented during challenging market condition effected by the long run Covid-19 pandemic.